Strategic Assessment of Sweden’s Water An exploratory study of municipal water supply, climate change, and population growth - Johansson, Hanna (My University, 2020)
Global water use is increasing due to economic development, changing consumption patterns, and population growth. Meanwhile, changes in temperature and precipitation as a result of climate change are expected to decrease water availability while further increasing the demand for freshwater. Sweden only uses a small percentage of its water resources but the resources vary regionally and several regions are already experiencing recurring water stress. In Sweden, the responsibility to supply drinking water in urban areas is assigned to the municipalities, which includes managing strategic planning and securing future water supply. This means managing the challenges of climate change and population growth, which are both complex issues. This thesis has been an exploratory study of climate change effects, population growth, and water supply focusing on the municipal supply in Sweden. By using literature, reports from governmental agencies and interviewing five case municipalities, four thesis questions have been analyzed. Thesis question 1: Where is water stress likely in Sweden under climate change and population growth? Thesis question 2: What are the consequences of water stress for water quality management? Thesis question 3: How well is Sweden equipped to cope with changes in water quantity and quality? Thesis question 4: What potential do different water supply technologies and other solutions have in the Swedish context? The thesis work has resulted in a water stress factor for thesis question 1, showing that water stress will occur in southeast Sweden, particularly around the Stockholm region. The analysis of thesis question 2 produced a compilation of unwanted water quality effects found in the literature, a handbook aimed at municipalities, and examples from the case municipalities. Increasing DOM and DOC concentrations were found to be a hot spot in the Swedish literature. The increasing concentrations of harmful microorganisms was the unwanted effect most frequently mentioned by the case municipalities. Thesis question 3 resulted in four important factors in the analysis of whether Sweden can cope with changes in water quantity: water availability, water treatment and delivery system capacity, population growth and demand, and intermunicipal cooperation. For thesis question 4, alternative solutions and technologies from the literature are presented along with the solutions and technologies used or potentially used by the case municipalities. The case municipalities were likely to stay with the current water supply technologies and the case municipality Gotland has the most experience with alternative solutions for water supply. Even though Gotland uses desalination plants to boost the supply, the interviewees believed water retention measures would be the best direction for future expansion of the municipality’s water supply.
Keywords: water supply; municipality; water resources; climate change; population growth; water quality